Salicylic acid and thiourea mitigate salinity and drought stress in wheat (Triticum aestivum) - YADAV, TARAMANI; YADAV, GAJENDER; KUMAR, ASHWANI; KUMAR, DINESH; YADAV, RK (The Indian Journal of Agricultural Sciences, 2022)
Water and salinity stresses are the major environmental concerns limiting crop production, particularly in arid and semi-arid ecologies. Focused research is required to develop mitigating strategies to manage such stresses. Application of plant-bioregulators (PBRs) may be an effective option to manage water and salinity stresses. Therefore, a field experiment was conducted during 2016–17 and 2017–18 at semi-arid saline site of NW (north-western) India to assess the effectiveness of salicylic acid and thiourea in easing out the adverse effect of variable water deficit and irrigation water salinity regimes. Increasing water deficit and its salinity significantly (P<0.001) reduced all the studied growth parameters, viz. plant height, crop stand, no. of tillers, leaf area index and relative growth rate; and yield attributes like no. of effective tillers, spike length, grains/spike, grain weight/spike, 1000-grain weight, specific weight. Application of either salicylic acid or thiourea significantly improved growth parameters in comparison to control and thiourea proved more effective. Thiourea application improved grain yield by 3.96 and 17.36%, biological yield by 4.21 and 14.82%, effective no. of tillers by 3.77 and 11.91%, weight/spike by 2.83 and 15.17%, 1000-grain weight by 3.72 and 12.66% and specific weight by 2.04 and 8.84% compared to salicylic acid and control, respectively. This might be due to better nutrient uptake, water relations, enhanced CO2 fixation and effective partitioning of assimilates. Thus, thiourea and salicylic acid application in wheat found better as compared to control under saline water stress.